1930
DOI: 10.1128/jb.19.2.117-124.1930
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Anaerobes in Crystal Violet Bile Media

Abstract: While experimenting with crystal violet bile media for use in water analysis, it was thought that some information could be obtained by testing the growth of anaerobes in media containing crystal violet and bile. An ideal medium for the detection of pollution in water supplies would be, of course, a medium which would prevent the growth of all bacteria except members of the colon group. This, however, is far from possible. B. welchii and other anaerobes are responsible for many false presumptive tests in water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1930
1930
1946
1946

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…A great amount of gas was produced in all of the media with a bile content greater than 1 percent even when the dye content was as great as 1: 1,000. The cultures of Type II were also found to be resistant to crystal violet as reported in a previous communication (2). The cultures of Type III and Type IV varied greatly.…”
Section: Brilliant Green Bile Mediasupporting
confidence: 73%
See 1 more Smart Citation
“…A great amount of gas was produced in all of the media with a bile content greater than 1 percent even when the dye content was as great as 1: 1,000. The cultures of Type II were also found to be resistant to crystal violet as reported in a previous communication (2). The cultures of Type III and Type IV varied greatly.…”
Section: Brilliant Green Bile Mediasupporting
confidence: 73%
“…He found, however, that the former strength afforded sufficient protection in most of the water supplies studied. One of us (2) while working with the crystal violet bile media found that a very high concentration of this dye was necessary to eliminate anaerobes. 'With a number of cultures of anaerobes a dye content greater than 1: 1000 was required to prevent growth and gas formation.…”
mentioning
confidence: 99%
“…Hall & Ellefson(2), and Salle(3) have proposed the addition of brilliant green, gentian violet, or crystal violet to the test medium as inhibitors, but Stark & England (4) found that this procedure suppressed some faecal coliform types. Poe (5) found that addition of bile salt to the medium did not eliminate anaerobes and sometimes encouraged their growth. However, Wilson (i), in an extensive, critical examination of the coliform test, states that bile salt-lactose broth yielded few false positives from water or milk, and this is probably the common experience in Britain.…”
mentioning
confidence: 99%
“…Later Oxley(i9) showed that such strains occur commonly in raw milk. (5) The existence of 'heat-resistant' coliforms, though of no significance as regards actual testing methods, may be important in dairy-plant control, and recently this problem has attracted some attention. The heat resistance of coliform organisms in milk had been studied by, among others, Ayers & Johnson (20), Tanner & Windsor (21), Wilson(i), and Vernon & Walker (22); in ropy milk by Hammer & Hussong(23); and in ice cream by Nelson et al (24) and Paley & Isaacs (25).…”
mentioning
confidence: 99%